2014
DOI: 10.1098/rsif.2013.1073
|View full text |Cite
|
Sign up to set email alerts
|

Analytical insights into optimality and resonance in fish swimming

Abstract: This paper provides analytical insights into the hypothesis that fish exploit resonance to reduce the mechanical cost of swimming. A simple body-fluid fish model, representing carangiform locomotion, is developed. Steady swimming at various speeds is analysed using optimal gait theory by minimizing bending moment over tail movements and stiffness, and the results are shown to match with data from observed swimming. Our analysis indicates the following: thrust-drag balance leads to the Strouhal number being pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Scaling parameters are of great importance in describing the dominant physics of locomotion. The Strouhal (St) number St(=f A/U) is one such parameter that has been used widely to characterize aquatic locomotion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] when the inertial fluid effects are dominant (high swimming velocities or large body sizes). The Strouhal number relates swimming speed U to the tail-beat frequency f and tail-beat amplitude (tip-to-tip excursion of the tail) A.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling parameters are of great importance in describing the dominant physics of locomotion. The Strouhal (St) number St(=f A/U) is one such parameter that has been used widely to characterize aquatic locomotion [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] when the inertial fluid effects are dominant (high swimming velocities or large body sizes). The Strouhal number relates swimming speed U to the tail-beat frequency f and tail-beat amplitude (tip-to-tip excursion of the tail) A.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, modeling and gait analyses within our framework have supported the hypotheses that carangiform fish exploit body-fluid resonance for efficient swimming [30] and two representative gaits of batoids, undulation and oscillation [31], result from energy optimization under round and triangular shapes of large pectoral fins [32], [33]. In the field of engineering, our framework is useful for proof-of-concept designs of mechanical rectifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that a natural walking stride conforms to the resonant frequency of the limbs when they are modeled as pendulums (Holt, Hamill, & Anders, 1991;Wagenaar & van Emmerik, 2000). Mathematical analysis of inertial swimmers (high Reynolds number swimming) supports the existence of resonance peaks when considering muscle tension (Kohannim & Iwasaki, 2014), travel speed, and efficiency (Gazzola, Argentina, & Mahadevan, 2015) with respect to frequency. Animals can also tune the resonance frequency of their bodies.…”
Section: Introductionmentioning
confidence: 86%